â€œVirtualâ€ v.s. â€œRealityâ€â€” On Taxing E-Sports Virtual Goods Transaction in Indonesia - Sung, Ming-Hsi; Umar, Wahyudi (Universitas Muhammadiyah Yogyakarta, 2020)
In technological advances, the emergence of various online games that have generated billion dollars has attracted the attention of the government currently. The most of its revenue comes from the sale of virtual item (item in-game) which have almost zero marginal cost of production. In 2019, Indonesia contributed 624 million dollars, equivalent to 8.7 trillion rupiah for mobile gaming.According to Mirza Adityaswara, Senior Deputy Governor of the Bank of Indonesia (BI), this phenomenon will bring the money out of Indonesia, then it makes Indonesia’s balance of trade (BOT) deficit.Indonesia’s BOT has been facing shortfalls in recent years. In 2019, the BOT decreased by 61.7%, the deficit reached -US1,933,90 million. This paper argue that Indonesia should take the case aquo as new tax base in order to resolve her deficit. An online game has its own currency which obtained through purchases using real money. This lead to trading real money for virtual objects, ‘land’ and ‘characters’ in-game. Uniquely, item in-game transaction is not only done by the developers to players but also players to players. Therefore, the phenomenon brings with it familiar legal issue such as sales tax. This paper intends to introduce the situation the current situation of case a quo in Indonesia and asserting the urgency and challenges of case aquo taxation in Indonesia.